Efficiency Strategy of Organic Matter Use for Soil Fertility and Productivity by Soil Biology Resources Empowerment - GITOSUWONDO, SUBOWO (Jurnal Sumberdaya Lahan, 2010)
Indonesia is an archipelago in wet tropical volcanic regions have high soil biodiversity, high rate of weathering and high of soil erosion, but low on soil fertility and soil organic matter content. Improvement of soil fertility to plant directly with the provision of organic materials requires a large amount and expensive. Problems faced by low organic matter production ability, high decomposition rate, bulky and is in the archipelago, making it difficult in the procurement and conservation of organic matter in soil and expensive transportation costs. Provision of organic materials with the aim of empowering the soil biology resources to enhance soil fertility potential pursued. In addition to the dose of organic matters required is relatively lower may also prevent the emergence of soil born diseases are also increasing of soil organic matter conservation. In determining land suitability evaluation in wet tropical volcanic region should consider the role of soil organism populations to support crop production and protected soil organic matter content.